Should we screen for atrial fibrillation? - Lown, M; Garrard, J; Irving, G; Edwards, D; Hobbs, F; Mant, J (Royal College of General Practitioners, 2017)
No country has yet established a national screening programme (NSP) for atrial fibrillation (AF), including the UK. However, there is an increasing body of evidence suggesting screening may be beneficial, prompting recommendations from prominent expert bodies to screen for AF.1 Despite these data, the UK National Screening Committee (NSC) has not recommended systematic population screening. The review in 2014 concluded ‘… it is not clear that those identified as at risk through screening would benefit from early diagnosis’.2 The NSC also identified a need to improve clinical management and standardise the treatment services currently available to those with diagnosed AF. The British Cardiovascular Society issued a subsequent statement in response to the decision questioning the interpretation of the evidence and suggesting that it would be in the public interest to reconsider their decision.3 A further review by the UK NSC is scheduled for 2017/2018.